(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, it is scientifically based that the institution of adoption is a humanitarian institution according to its essence and purpose. It has been revealed from a socio-legal point of view that it is necessary to focus on providing normal family education to children who are deprived of their parents or cannot receive parental education for some reasons. A child who has lost his parents due to adoption is placed in another family and given family education.